Estudo de primeiros princípios em nanotubos de carbono interagindo com NO2SbF6 - Sabino, Adelmo Santiago (2006)
In this work we present the study of the interaction of the nitronium hexafluorantimonate (NO2SbF6-NHFA) with nanotubos of carbon (5,5), (8,0) and bundles of nanotubos of carbon (8,0). The treatment of nanotubos in TMS/cloroforme solution (tetramethylene sulfone/chloroform) with NO2SbF6 is responsible for the formation of superbundle. To study the structural and electronic properties in the considered systems, we use an established theoretical boarding in calculations of first principles, making use of the theory of the functionary of the density with the approach of the local density for the term of exchange–correlation. The calculations had been carried through using computational program SIESTA. In order to analizarmos the interaction of the nanotubos and bundles of carbon with the NHFA, investigate ion NO+2 , anion SbF− 6 and the molecule NO2SbF6 interacting with the nanotubos or intercalated in bundles of nanotubo of carbon. From the electronic and estrural characterization we evidence that the systems formed for nanotubos of carbon (5,5) and NO+2 , (8,0) and NO+2 interact way strong chemical adsorption, while the other systems interact way weak chemical adsorption.